Reverse logistics of waste tires in Brazil: a proposal for collaborative monitoring - Teixeira, Létison Elias; Milkievicz, Indianara Ignacio; Fagundes, Alexandre Borges; Beuren, Fernanda Hänsch; Vaz, Caroline Rodrigues; Kobs, Fábio Fernando; Vieira, Cleide (OBSERVATÓRIO DE LA ECONOMÍA LATINOAMERICANA, 2025)
THIS IS AN ARTICLE PUBLISHED BY OBSERVATÓRIO DE LA ECONOMÍA LATINOAMERICANA (e-ISSN: 1696-8352) ON 2025-05-21, AVAILABLE ONLINE: https://doi.org/10.55905/oelv23n5-112 Abstract This article develops a study on current inspection practices for the proper disposal of unusable tires, aiming to identify flaws and collaboratively propose a solution involving all entities related to this type of product. As noted in recent literature, a law exists that needs to be enforced, but complete compliance monitoring is not feasible. Therefore, the goal of this research was to propose a solution based on an audit model similar to those used in Quality Management Systems within the automotive industry. Applying the concepts and audit practices of quality management, adapted to environmental inspection, has proven effective in identifying gaps and proposing an integrated model. This demonstrates that expanding the scope of inspection can lead to a more robust and efficient system. Such improvements can benefit both the environment and organizations that reuse these materials. The importance of this proposal is heightened by the current consumption trends, which threaten environmental stability.
Keywords: Waste Tires; Inspection; Audit; Quality Management System; Reverse Logistics